The Swedish budget 1974/75 - Sweden (Stockholm: Ministry of Finance, 1974)
This twelfth edition of The Swedish Budget contains a summary of the draft budget for the fiscal year 1974/75, with more detailed reviews of the main items of government expenditure. The budget statement is a translation of the complete Swedish text.
A summary published by the ministry of Finance
Includes bibliographic references
rpm 20/02/2019
Ref
Keywords: Budget; Budget; Economic history; Sweden; Sweden